Drug utilization study in the inpatients of pediatric department of a tertiary care hospital - Chavda, Dinesh A.; Mistry, Rusva A.; Solanki, Krunal C.; Suthar, Satish D.; Desai, Bharti L.; Mistry, Suresh D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Infants and children constitute a large proportion of the population in developing countries. In Gujarat, studies on drug use patterns in the pediatric age group are lacking in the Saurashtra region hospitals. The objective was to study demographical information and the utilization pattern in the in patients of the pediatric ward. Methods: A cross-sectional, observational drug utilization study was carried out over a period of 6 months in 630 pediatric inpatients of the pediatric department of Guru Gobind Singh Hospital, Jamnagar, a tertiary care teaching hospital. Analyzed data included demographic details and drugs prescribed in respective patients. Results: Most commonly affected age group was 1-5 years, boys in 62.06% and girls in 37.94% and 40.16% were admitted in the pediatric ward. Acute gastroenteritis and pneumonia had the highest admission rate with 31.90% and 22.38%, respectively. The majority of children were prescribed 5-6 drugs. Ceftriaxone (64.92%) was the top most frequently prescribed antibiotic, followed by amoxicillin (49.21%). Prescribing drugs were mainly from essential drug list (64.44%) and by generic names (61.89%). Drugs prescribed orally in 66.10% and by injections in 33.90%. Conclusion: It is quite evident that significantly large number of children were from 1 to 5 year age group. The majority of the children were admitted in inpatients of the pediatric ward for acute gastroenteritis, followed by pneumonia and meningitis. Most frequently prescribed antibiotic group was cephalosporin, followed by penicillin group.